HERMANSKY-PUDLAK SYNDROME AND GRANULOMATOUS BOWEL INFLAMMATION - REVIEW ARTICLE AND CASE REPORT - Urška Berden; Lidija Kitanovski; Darja Urlep (The Society for Children with Metabolic Disorders, 2022)
Hermansky-Pudlak syndrome (HPS) is a very rare genetically and phenotypically heterogeneous multisystemic disorder. It is mainly caused by impaired trafficking to lysosome-related organelles. Eleven genetic subtypes of HPS are currently recognised. All subtypes share the common phenotypic features of oculocutaneous albinism and a bleeding diathesis due to thrombocyte dysfunction. Accumulation of ceroid lipofuscin in the reticuloendothelial system of different organs is also common. In some subtypes of HPS, especially in HPS-1 and HPS-4, Crohn's disease - like granulomatous bowel disease can develop. In this article, the only case of a girl with HPS-1 and granulomatous bowel disease diagnosed in Slovenia is presented. She has colitis of the small and large bowel, with clinical, endoscopic, and histopathological characteristics of Crohn's disease.